Parental Involvement during Pandemic Times: Challenges and Opportunities - Luísa Mota Ribeiro; Rosário Serrão Cunha; Maria Conceição Andrade e Silva; Marisa Carvalho; Maria Luísa Vital (Education Sciences, 2021)
Due to COVID-19, many countries implemented emergency plans, such as lockdown and school closures. This new situation has significantly affected families, namely, the involvement required to support children’s learning at home. The current study aimed to analyze Portuguese parents’ perceptions of their home-based parental involvement in their children’s learning during the lockdown and school closures in 2020 due to COVID-19. An online survey, using a closed-ended questionnaire, was employed. Variables included parents’ sociodemographic and COVID-19 related characteristics; students’ sociodemographic characteristics; distance learning context; parental involvement; and students’ autonomy. Data were collected from a sample of 21,333 parents with children from elementary school to secondary education, and statistical data analysis was performed using IBM SPSS Statistics 26. Findings revealed that Portuguese parents supported their children during the pandemic mainly through the monitoring of attention in classes and task realization. However, several variables appear to significantly determine parental involvement time, which is higher when students attend public schools, when they are less autonomous and younger, when parents’ level of education is lower, when the child is a boy (except in secondary education where gender is not relevant), and when the online school time is higher. Findings highlight the need for a significant investment of time from parents, particularly of primary school children, making it difficult to cohere work or telework with school activities. Implications for policies, schools, families are discussed in order to promote children’s learning and success.